Legal-Political Reform for Indigenous Peoples’ Rights Based on Maslahah Principles (Jurnal Hukum Islam, 2026)
The rights of indigenous peoples have been normatively recognized but remain ambiguous, triggering marginalization, agrarian conflict, criminalization, and the loss of their living space. This study analyzes legal ambiguity and its implications for protecting indigenous peoples’ rights and makes legal-political reforms based on the maslahah principle. This study adopts a normative legal method with a statutory, conceptual, and philosophical approach based on Islamic law. The research findings indicate that the ambiguity of norms in the recognition and protection of indigenous peoples’ rights has created legal uncertainty and strengthened the dominance of state and corporate economic-political interests over indigenous territories. Disharmony in sectoral regulations and the lack of recognition of indigenous peoples as legal subjects have weakened their collective rights’ protection. The orientation of agrarian legal politics, emphasizing administrative and procedural approaches, has not fully achieved substantive justice in the protection of indigenous peoples’ rights. This study provides a legal-political reform model based on the maslahah principle as a philosophical foundation for national legal reform, oriented toward protecting the public interest and preventing harm. The reform model is directed through the integration of Islamic legal values into the national legal system, strengthening the constitutional and regulatory recognition of indigenous communities, harmonizing agrarian and sectoral regulations, and affirming collective rights to indigenous territories. Through this framework, the protection of indigenous peoples’ rights will be realized in a just, legally certain, responsive, and public welfare-oriented manner.
Keywords: Agrarian conflict; Customary land rights; Indigenous peoples; Maslahah; Substantive justice